Experimental Approach of Thermal Management Properties for Phase Change Materials in Energy Storage Modules at Different Power Loading - Somek, Kutlu; Papurello, Davide; Bressan, Maurizio; Campagnoli, Elena; Fina, Alberto; Derun, Emek (WILEY, 2026)
Efficient thermal management of lithium-ion batteries is essential to increase safety, extend service life and improve operating range, while ensuring stable performance in electric vehicles. Although phase change materials (PCMs) have been extensively studied in the context of thermal control systems, systematic experimental evaluations conducted on commercially available pure PCMs are still limited. This study experimentally analyses the thermal performance of pure PCMs with melting points of 42 degrees C, 47 degrees C, and 57 degrees C by subjecting them to thermal loads of 20, 40, and 80 W in a simulated energy storage module based on a 2S2P configuration of 18 650 cylindrical cells. The thermal response of the system was monitored using thermocouples and infrared thermography, while the thermophysical properties of the PCMs (latent heat, specific heat, and thermal conductivity) were characterized using DSC calorimetry and thermal conductivity analysis. To assess material reliability, all PCMs were subjected to 100 consecutive thermal cycling tests. Based on module-level results, the most effective PCM was further validated through 2C charge-discharge cycling of a commercial lithium-ion cell, followed by post-cycling structural examination using X-ray micro-computed tomography. The results demonstrate that PCM integration reduces maximum operation temperatures by up to 40 degrees C-60 degrees C compared to the reference case without PCM, depending on the thermal load. Among the tested materials, PCM with a melting point of 47 degrees C showed the most balanced performance, providing temperature uniformity, extended delay times and stable behavior under both thermal and electrochemical cycling. Overall, the results confirm that pure PCMs are a practical solution to improve the safety and thermal stability of electrochemical storage systems.
Keywords: battery; battery safety; energy storage; phase change materials; thermal management; Energy & Fuels